High triglyceride is a risk factor for silent osteonecrosis of the femoral head in systemic lupus erythematosus. Issue 12 (December 2015) - Kuroda, Takeshi; Tanabe, Naohito; Wakamatsu, Ayako; Takai, Chinatsu; Sato, Hiroe; Nakatsue, Takeshi; Wada, Yoko; Nakano, Masaaki; Narita, Ichiei
Abstract The purpose of this study was to clarify the factors related to silent osteonecrosis of the femoral head (ONFH) in patients with systemic lupus erythematosus (SLE). Seventy-eight patients with SLE were selected on the basis of having been newly diagnosed and requiring high-dose prednisolone, including pulse therapy with methylprednisolone, as the initial treatment. All the patients initially underwent MRI at 3 months after the start of corticosteroid treatment to detect any early changes in the femoral head. These examinations were then performed again 3 months later. Laboratory parameters were evaluated at the start of steroid treatment and at 1 month thereafter. By 3 months after the start of corticosteroid treatment, silent ONFH was diagnosed by MRI in 21 patients (26.9 %), being bilateral in 11 patients and unilateral in 10. The occurrence of silent ONFH was not related to SLE disease activity index, serological activity, or renal function; it was also unrelated to body mass index (BMI), body surface area (BSA), and the initial dose of prednisolone per unit body weight. However, the total cholesterol level at 4 weeks after the start of steroid treatment tended to be higher in patients with silent ONFH. Patients with a higher triglyceride level showed a significantly higher frequency of silent ONFH both before (p  = 0.002) and 4 weeks after (p  = 0.036) steroid initiation. A high triglyceride level is an important risk factor for silent ONFH in patients with SLE, and large-scale epidemiologic surveys of such early events are needed in this patient population.